Breast lumps and lymphoma. Issue 716 (June 1985) - Ellis, M.; Arno, J.; Owen-Smith, M.; Sikora, K.
Abstract : We report two cases of young women in whom a breast lump was the first symptom of disseminated lymphoma. They were managed by wide excision of the affected segments of breast. Histological diagnosis was aided by immunoperoxidase stains for immunoglobulin chains. Further investigations demonstrated the wide spread nature of the disease, with involvement of bone marrow, bone cortex, lymph nodes and lung. Both patients received systemic chemotherapy, which achieved complete remission in one.